Teaching pediatric communication skills to medical students - Frost, Katherine A (Adv Med Educ Pract, 2015)
BACKGROUND: Delivering effective clinical pediatric communication skills training to undergraduate medical students is a distinct and important challenge. Pediatric-specific communication skills teaching is complex and under-researched. We report on the development of a scenario-based pediatric clinical communication skills program as well as students’ assessment of this module. METHODS: We designed a pediatric clinical communication skills program and delivered it five times during one academic year via small-group teaching. Students were asked to score the workshop in eight domains (learning objectives, complexity, interest, competencies, confidence, tutors, feedback, and discussion) using 5-point Likert scales, along with free text comments that were grouped and analyzed thematically, identifying both the strengths of the workshop and changes suggested to improve future delivery. RESULTS: Two hundred and twenty-one of 275 (80%) student feedback forms were returned. Ninety-six percent of students’ comments were positive or very positive, highlighting themes such as the timing of teaching, relevance, group sizes, and the use of actors, tutors, and clinical scenarios. CONCLUSION: Scenario-based teaching of clinical communication skills is positively received by students. Studies need to demonstrate an impact on practice, performance, development, and sustainability of communications training.